Yevgeny Anatolijovych Pobel - Multidisciplinary Clinical Hospital № 9, Zaporizhia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to the memory of the outstanding scientist Ye. A. Pobel.